Analisis Akuntabilitas Pengalokasian Dana Hibah Pemkab Jombang Untuk TPQ Di Desa Sengon - Vega Septian Fikri D; Mohamad Djasuli (CV. ITTC INDONESIA, 2022)
This grant is a form of concern from the Jombang district government to social organizations and religious institutions, especially worship facilities and infrastructure, both prayer rooms and mosques and churches (TPQ). However, for the beneficiaries of these grants, there is usually an imbalance in the budget because there are many factors that influence it so that there are many funds that are not distributed evenly to TPQ institutions, so this has an impact on the uneven distribution of these grants. Proposals and files in accordance with what was requested by the Jombang Regency Government, if the files have been validated, can be used to account for the allocation of facilities and infrastructure activities in the LPJ (accountability report), which contains minutes of the disbursement of grant funds, a realization report of fund allocation grants, and some receipts that can later be shown to the Jombang Regency Government. These are in accordance with existing regulations and funds that have been used as efficiently as possible and are accountable. The suggestions and infrastructure must be carried out in accordance with what was submitted in the proposal, so that the management of religious institution development is created in accordance with what is expected. Empowering the development of non-formal religious education for TPQ.